The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000505553
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Electroconvulsive Therapy in the Treatment of Major Depressive Disorder

Abstract: <b><i>Background/Aims/Methods:</i></b> Electroconvulsive therapy (ECT) is still one of the most potent treatments in the acute phase of major depressive disorder (MDD) and particularly applied in patients considered treatment resistant. However, despite the frequent and widespread use of ECT for &#x3e;70 years, the exact neurobiological mechanisms underlying its efficacy remain unclear. The present review aims to describe differential antidepressant and cognitive effects of ECT as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Emerging evidence has indicated an association between inflammation and depression in older patients ( 37 ). Recent studies corroborate that higher baseline inflammation is associated with a poor response to pharmacological antidepressant therapies ( 38 ). Studied have reported conflicting findings regarding the effects of ECT on serum pro-inflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 78%
“…Emerging evidence has indicated an association between inflammation and depression in older patients ( 37 ). Recent studies corroborate that higher baseline inflammation is associated with a poor response to pharmacological antidepressant therapies ( 38 ). Studied have reported conflicting findings regarding the effects of ECT on serum pro-inflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 78%
“…In particular, the rationale for these investigations came from the observation of inflammatory and immune dysfunction in patients with MDD, such as increased levels of cytokines including the interleukins 6 (IL-6) and 1-Beta (IL-1β), the tumor necrosis factor-alpha (TNF-α), and the C-reactive protein (CRP), especially in TRD, for which ECT represents one of the most effective treatments. Moreover, higher baseline inflammation has been linked to a decreased response to pharmacological antidepressant therapies [ 80 ].…”
Section: Inflammatory and Immune Systemsmentioning
confidence: 99%
“…Overall, these reviews showed contradictory results regarding the fluctuation of different inflammatory markers after a course of ECT. Another inconsistency was described by Stippl et al 19 (2020) who reported that an elevation of serum brain-derived neurotrophic factor levels has also been observed by several studies, whereas others have found decreased levels or no alterations in this inflammatory marker after ECT.…”
mentioning
confidence: 93%